FIELD CORPORATE STRATEGY PLANNING TOURISM AT INJOURNEY (PT AVIATION TOURISM INDONESIA PERSERO) - Tia Riska Ayunda; Waznah; T.Arif Alfarizi; Zikrullah Deyan Putra (RADJA PUBLIKA, 2023)
Corporate strategy is an overall strategy or integrated strategy that is determined based on the coordination of all fields within the company. The purpose of forming an organization is to achieve the goals of both public organizations and private organizations. This study aims to determine the corporate strategy of SOE Injourney (PT Aviasi Wisata Indonesia) Persero. Indonesian Journey or Injourney is a BUMN holding for the Indonesian Aviation and Tourism industry which is under the auspices of PT Aviation Tourism Indonesia (Persero). The function of this company is to carry out business activities as a holding company in the field of tourism and support. The research method used is a qualitative method with a literature analysis study approach.